Policy of the Booster Vaccination Program for Prospective Hajj Congregations Perspective on the Effectiveness of Delivery in Pandemic Times - Ivan Elisabeth Purba; Parlindungan Purba; Rahmat Alyakin Dakhi (Budapest International Research and Critics University, 2022)
The government's policy through the COVID-19 vaccination program in Indonesia which began to be implemented on January 13, 2021 can accelerate the occurrence of herd immunity which will have an impact on reducing the number of infected cases so that prospective pilgrims whose departure has been postponed since 2019 can leave. perform the pilgrimage. The World Health Organization (WHO) explained that vaccine performance can be seen from three measurements, namely through the efficacy, effectiveness, and impact of the vaccine. The booster vaccination program policy can be carried out effectively because it is a mandatory requirement for prospective Hajj pilgrims. However, the effectiveness of deferred departures does not work as well as the implementation of the vaccination program regulated by the government, so the government must continue to make educational efforts and encourage active community involvement to comply with the COVID-19 health protocol. The research was conducted using the literature study method by collecting related data throughout the pandemic period in Indonesia.